Relationship between exchange rate volatility and interest rates evidence from Ghana - Sarpong Mohammed; Abubakari Mohammed; Edward Nketiah-Amponsah (Cogent Economics & Finance, 2021)
This paper examines the effect of interest rates on exchange rate volatilities in Ghana. It utilizes the Quarterly Time Series dataset spanning 2000 Quarter 1 to 2017 Quarter 2 and the Autoregressive Distributed Lag model as well as the Vector Error Correction Model to investigate the long-run and short-run relationships between the variables. The results showed that in the long-run model, exchange rate volatility was seen to be influenced by money supply, inflation, Central Bank's policy rate, and the Ghana Stock Exchange composite index. However, in the short-run model, exchange rate volatility was found to be significantly influenced by its past values and the Central Bank's policy rate.
Keywords: 330; autoregressive-distributed lag; Exchange rate volatility; interest rate